Never the right time: maternity planning alongside a science career in academia - EREN, EBRU (My University, 2020)
Pregnancy and maternity planning pose a challenge and stress in the academic career of a researcher, especially at the PhD and postdoctoral level, where the conditions of employment and role status are not clear. This paper discusses how women evaluate maternity-related issues and balance their scientific career in the field of physics and the physical sciences from undergraduate to postdoctoral level. The paper tries to assess how this affects their progress in academic science. The data were generated through in-depth individual interviews with 15 women from four universities in Dublin. The participants of this study were not necessarily mothers or mother-to-be. The findings indicate that compared to their male counterparts, the need to continually publish, the absence of paid parental leave, short-time positions, lack of clear institutional policies on maternity, lack of pregnancy-maternity friendly work plans and the non-extension of contracts, puts many female early-career scientists at an academic disadvantage, resulting in a leaky pipeline. This paper will offer a wider understanding of how instability intersecting with maternity, gender and gendered family responsibilities cause young women from undergraduate to postdoctoral level in science to re-evaluate their academic career progression.
Keywords: Academia; Maternity; Parental leave; Researchers; Science; Identities in Transformation; EDUCATION; Gender and work; Motherhood; Sociology; Women's Studies; Women's studies; Education; Gender